Inspection of Sanitary Indicator Bacteria in The Pacific White Shrimp (Litopeneaus vanamei) Pond Culture, Trang Province for Developing a Safety Culture System - Lohalaksanadech, Dumrong; Sajarit, Chutinut (Progress in Applied Science and Technology, 2016)
The sanitary indicator bacteria from bottom soil, water and pacific white shrimp (Litopeneaus vanamei) in shrimp pond was determined from May to August 2015 on 8 shrimp ponds. All samples were inspected for total coliforms (TC), fecal coliforms (FC), fecal streptococci (FS) and Salmonella. Most of samples were found that TC, FC and FS from soil and shrimp were less than 3 MPN/g. Pond-water samples were found 0-10 MPN/100 ml. Faecal Streptococci group was examined : Enterococcus faecium, E. faecalis and E. casseliflavus from bottom soil and pond-water; E. faecalis and E. casselitflavus form shrimp. Salmonella was examined: Salmonella javianaand Salmonella brunei, but Salmonella was not detected from shrimp samples.